Educating Roma children. Going beyond integration - DROWN, Rosa (Presa Universitară Clujeană, 2020)
Some years ago, when in Romania, I was asked for help by a charity representing Roma families. The families told me that their children attended school but apparently learned nothing. At this time many of the traditional occupations of Roma families such as skilled craft work and agricultural labouring had disappeared as such occupations had been taken over by factory made products or agricultural machines. This meant that it was essential for their children to be able to read and write in order to obtain employment after they had left school. School directors and teachers also told me that Roma children were attending school in increasing numbers but they seemed unable to teach them successfully. They also asked me for help. Although I am experienced teacher who had already carried out projects in different Romanian schools, I had no ready solutions for the families or the schools, even following visits to different villages and schools, including those that had participated in European Union funded projects for improving education for Roma. I also talked to other experts involved with Roma education, read reports and research literature which also covered other countries; however, I was unable to discover any ready solutions that proved to be successful over the long term.